Is There a Dark Side to Work Passion? Insights on Well-Being and Performance in the Evolving Knowledge Economy - Annamalai, Sumathi; Prashar, Gaorisha; M., Mallika Sankar (Prabandhan: Indian Journal of Management, 2025)
Purpose : Work passion (WP) inspires employees to discover more profound meaning and fulfilment in their careers. However, is there a dark side to WP? This paper aimed to explore the answer to this question and test the mediating role of employee well-being in the relationship between WP and perceived performance. Design/Methodology/Approach : We employed a quantitative survey method, and 107 executive-level leaders, referred to as CXOs, participated. We administered the WP Scale, developed by Vallerand et al. (2003), further modified to suit the workplace by Ho et al. (2011), the Employee Wellbeing Scale developed by Pradhan and Hati (2019), and the Perceived Performance Scale developed by Karneli et al. (2015) for collecting data. We used Process MACRO (Model 4) for mediation analysis. Findings : The conclusions of the study indicated that while obsessive passion (OP) had a negative impact on workers’ well-being, harmonious passion (HP) had a positive influence on employee well-being. Both HP and performance, as well as OP and performance, were mediated by well-being. HP positively impacted performance, while performance was negatively impacted by OP. Practical Implications : The findings have numerous advantages for executive-level leaders, allowing them to strengthen employee well-being and organizational performance. They should first concentrate on creating a positive environment at work that encourages an HP. Second, the adverse impacts of OP on performance and well-being can be minimized by using programs designed to promote mental health, such as stress management tools and wellness initiatives. Originality/Value : This paper added to the body of research and knowledge by distinguishing between the different types of consequences (both positive and negative) of WP on employee well-being and performance. Organizational leaders, particularly CXOs, can gain insights from the paper’s contributions regarding the significance of creating a supportive work environment that maximizes HP and prevents obsessive behavior.